Lithium-ion and lithium-sulfur batteries : fundamentals to performance - Arote, Sandeep A. (IOP (Series). Release 22., 2022)
This research text explores the fundamentals, working mechanisms, electrode materials, challenges, and opportunities for energy storage devices of lithium-ion and lithium-sulfur battery technology.